Colombia : Financial Sector Assessment Program-Technical Note-Crisis Management, Resolution, and Safety Nets. (IMF Staff Country Reports; Country Report ;, 2022)
The first mission of the Colombia FSAP was conducted virtually during June 1-21, 2021. This technical note focuses on the developments in the crisis management framework for the banking sector. The assessment examines the Colombian financial safety net and crisis management arrangements in light of the international best practices and standards on resolution and deposit insurance standards.